Diagnostic utility of reticular iris pattern for identifying cytomegalovirus-associated Posner-Schlossman syndrome - Nhat B. D. Huynh; Duyen T. U. Nguyen; Nguyen L. H. Nguyen; Huy D. M. Tran (Graefe's Archive for Clinical and Experimental Ophthalmology, 2026)
Abstract Purpose This study aimed to evaluate the association between the reticular iris pattern and cytomegalovirus (CMV) positivity detected by aqueous humour polymerase chain reaction (PCR) testing in Posner-Schlossman syndrome (PSS) and to estimate its diagnostic performance. Methods Thirty patients with active PSS at a tertiary eye centre in Vietnam underwent aqueous humour polymerase chain reaction (PCR) testing and anterior segment assessment. Firth penalized logistic regression identified clinical signs associated with CMV positivity, and diagnostic performance metrics were calculated. Results CMV was detected in 46.7% (14/30) of cases. Reticular iris pattern was associated with CMV positivity (OR = 17.85, 95% CI 3.05-197.14, p < 0.001), present in 64% of CMV-positive versus 6% of CMV-negative cases, with 64.3% sensitivity, 93.8% specificity, and 90.0% positive predictive value. Stellate keratic precipitates were less sensitive but also associated with CMV (OR = 14.14, p = 0.027), demonstrating high specificity (100.0%, 95% CI 79.4%-100.0%). CMV-positive patients also showed higher rates of glaucomatous damage (85.7% vs. 18.8%, p < 0.001). Conclusions Reticular iris pattern demonstrated high specificity for CMV-associated PSS in our cohort. Recognition of this sign during slit-lamp examination may help prioritise aqueous PCR testing, but the sign should not replace virological confirmation. Validation in larger, prospective cohorts is warranted.